If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8+2(x+1)=3(x+1)
We move all terms to the left:
8+2(x+1)-(3(x+1))=0
We multiply parentheses
2x-(3(x+1))+2+8=0
We calculate terms in parentheses: -(3(x+1)), so:We add all the numbers together, and all the variables
3(x+1)
We multiply parentheses
3x+3
Back to the equation:
-(3x+3)
2x-(3x+3)+10=0
We get rid of parentheses
2x-3x-3+10=0
We add all the numbers together, and all the variables
-1x+7=0
We move all terms containing x to the left, all other terms to the right
-x=-7
x=-7/-1
x=+7
| 6^x-2=1/1296 | | 2x+6(x-7)=30 | | n-3/4=23/4 | | -m=-60 | | 2x/3+x=500000 | | 3x-9/9=1/3+x/2 | | 19-z=8 | | -9(2d+9.5)=24.5+8d | | 9-x2=0 | | 8/3+8=2/3x+24 | | -24=c+-29 | | -2y+9=-3(y+4) | | -6(2x-1)+1=-12x+7 | | 5x+4(x-7)=53 | | 39/5=3m | | 8/3x+8=2/3x+24 | | -6+x/4=6 | | 5(-2+y)-3(y-1)=2 | | -31s=465 | | 1+2(x-1)=4 | | 1+6n=25 | | (15-6x)(5+2x=720x | | 20-4x^2=12 | | 23–3z=–4 | | 2(x-1)=5+5(x+2) | | 16x-10x-8=0 | | -3+32+5x=-42 | | 25=1/x(50) | | 7+x²=11 | | 5(2-y)-3(y-1)=2 | | 10x-2/3=24x-14x+-7 | | 4(x+4)=-7+2(1+2x) |